2016
DOI: 10.1159/000451077
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Coping Strategy Changes in Multiple Sclerosis Patients Initiating Fingolimod: The GRACE Prospective Study

Abstract: The objective of this prospective study was to assess the changes in anxiety levels, and their relationship with coping strategies over the first four months of fingolimod treatment in patients with relapsing remitting multiple sclerosis (RRMS). Data were collected at the inclusion visit (Visit 1) and 4 months later (Visit 2). We used the Hospital Anxiety and Depression Scale (HADS) to assess the level of anxiety and the Coping Inventory for Stressful Situations scale to assess the coping strategies used when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The clear anxiolytic effects of fingolimod suggest that this pathway provides new targets for anxiety drug development and demonstrate the possibility of repurposing existing drugs to anxiety therapy. In this context, a prospective study described a decrease in anxiety levels in multiple sclerosis patients upon initiation of fingolimod treatment ( Moreau et al., 2017 ). Current therapies for anxiety disorders either directly affect neurotransmitter receptor systems or modulate neurotransmitter levels or availability, but their long-term use is limited by problematic side effects and suboptimal efficacy ( Griebel and Holmes, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clear anxiolytic effects of fingolimod suggest that this pathway provides new targets for anxiety drug development and demonstrate the possibility of repurposing existing drugs to anxiety therapy. In this context, a prospective study described a decrease in anxiety levels in multiple sclerosis patients upon initiation of fingolimod treatment ( Moreau et al., 2017 ). Current therapies for anxiety disorders either directly affect neurotransmitter receptor systems or modulate neurotransmitter levels or availability, but their long-term use is limited by problematic side effects and suboptimal efficacy ( Griebel and Holmes, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including the five studies which provided the necessary information also found that depression improved ( Fig. 4A, SMD [95%CI]; 1.18 [0.17, 2.19]) (Bayas et al, 2016;Hersh et al, 2017;Hunter et al, 2016;Moreau et al, 2017;Popova et al, 2017). High heterogeneity existed between estimates (I 2 99%; p = 0.0001).…”
Section: Fingolimodmentioning
confidence: 84%
“…Eight publications, representing six unique studies (2 observational, 4 RCTs) examined changes in depression symptoms following fingolimod treatment using various tools (Achiron et al, 2017;Bayas et al, 2016;Calkwood et al, 2014;Fox et al, 2014;Hersh et al, 2017;Hunter et al, 2016;Montalban et al, 2011;Moreau et al, 2017;Popova et al, 2017). In all studies, depression symptoms improved following fingolimod treatment.…”
Section: Fingolimodmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, fingolimod has been also shown to decrease anxiety [ 204 ] and improve depressive symptoms in MS treated patients [ 205 ]. Studies in mice further supported a protective role for fingolimod upon chronic stress exposure [ 206 ] in a neurogenesis dependent way [ 207 ], as a facilitator of fear memory extinction [ 208 ] and in reversing the anxiety-like behavior induced by the regional expression of α-importin 5 in the ventral hippocampus [ 209 ].…”
Section: Sphingolipids In Psychiatric Diseasesmentioning
confidence: 99%